Dual‐excitation flip‐angle simultaneous cine and T1 mapping using spiral acquisition with respiratory and cardiac self‐gating. Issue 1 (15th February 2021) - Zhou, Ruixi; Weller, Daniel S.; Yang, Yang; Wang, Junyu; Jeelani, Haris; Mugler, John P.; Salerno, Michael
Abstract : Purpose: To develop a free‐breathing cardiac self‐gated technique that provides cine images and B 1 + slice profile–corrected T 1 maps from a single acquisition. Methods: Without breath‐holding or electrocardiogram gating, data were acquired continuously on a 3T scanner using a golden‐angle gradient‐echo spiral pulse sequence, with an inversion RF pulse applied every 4 seconds. Flip angles of 3° and 15° were used for readouts after the first four and second four inversions. Self‐gating cardiac triggers were extracted from heart image navigators, and respiratory motion was corrected by rigid registration on each heartbeat. Cine images were reconstructed from the steady‐state portion of 15° readouts using a low‐rank plus sparse reconstruction. The T 1 maps were fit using a projection onto convex sets approach from images reconstructed using slice profile–corrected dictionary learning. This strategy was evaluated in a phantom and 14 human subjects. Results: The self‐gated signal demonstrated close agreement with the acquired electrocardiogram signal. The image quality for the proposed cine images and standard clinical balanced SSFP images were 4.31 (±0.50) and 4.65 (±0.30), respectively. The slice profile–corrected T 1 values were similar to those of the inversion‐recovery spin‐echo technique in phantom, and had a higher global T 1 value than that of MOLLI in human subjects. Conclusions: Cine and T 1 mapping using spiral acquisition with respiratory and cardiac self‐gating successfully acquired T 1 maps and cine images in a single acquisition without the need for electrocardiogram gating or breath‐holding. This dual‐excitation flip‐angle approach provides a novel approach for measuring T 1 while accounting for B 1 + and slice profile effect on the apparent T 1 ∗ .